Cirrhotic Endothelial Progenitor Cells Enhance Liver Angiogenesis and Fibrosis and Aggravate Portal Hypertension in Bile Duct-Ligated Cirrhotic Rats - Tripathi, Dinesh Mani; Hassan, Mohsin; Siddiqui, Hamda; Kaur, Impreet; Rawal, Preety; Bihari, Chaggan; Kaur, Savneet; Sarin, Shiv K. (Frontiers in Physiology, 2020)
Background Circulating cirrhotic endothelial progenitor cells (EPC) interact with both liver sinusoidal endothelial cells (LSEC) and hepatic stellate cells (HSC) and promote angiogenesis in vitro. This study evaluated the effect of cirrhotic and control EPCs on hepatic angiogenesis, microcirculation, and fibrosis in vivo in rat models of cirrhosis. Methodology Animal models of cirrhosis were prepared by bile duct ligation (BDL). Circulating EPCs isolated from healthy human and cirrhotic blood were characterized by flow cytometry, cultured and administered through the tail vein in BDL rats after 2 weeks of ligation. The cells were given thrice a week for 2 weeks. The untreated group of BDL rats received only saline. Fibrosis was evaluated by Masson’s trichrome staining. Dedifferentiated LSECs were identified by the expression of CD31, and activated HSCs were marked as alpha-SMA-positive cells and were studied by immunohistochemistry and western blotting in saline-, healthy EPC-, and cirrhotic EPC-treated rats. In vivo, hepatic and systemic hemodynamic parameters were evaluated. Liver functions were evaluated. Results In comparison to controls, BDL rats revealed an increase of fibrosis and angiogenesis. Among the treated rats, cirrhotic EPC-treated rats had increased fibrosis grade as compared to healthy EPC-treated and saline-treated rats. There was an increase of both fibrosis and angiogenesis markers, alpha-SMA and CD31 in cirrhotic EPC-treated rats as compared to healthy EPC-treated and saline-treated rats in immunohistochemistry and western blot studies. Cirrhotic EPC-treated BDL rats had high portal pressure and portal blood flow with significantly elevated hepatic vascular resistance in comparison with healthy EPC- and saline-treated BDL animals, without significant differences in mean arterial pressure. Cirrhotic EPC-treated BDL rats also showed a substantial increase in the hepatic expression of angiogenic receptors, VEGFR2 and CXCR4 in comparison with saline-treated rats. Conclusion The study suggests that transplantation of cirrhotic EPCs enhances LSEC differentiation and angiogenesis, activates HSCs and worsens fibrosis, thus resulting in hepatic hemodynamic derangements in BDL-induced cirrhosis.